2020
DOI: 10.3390/su122410434
|View full text |Cite
|
Sign up to set email alerts
|

Universalists or Utilitarianists? The Social Representation of COVID-19 Pandemic in Brazil

Abstract: A fierce debate arose in Brazil on how to manage and mitigate the coronavirus disease 2019 (COVID-19) pandemic—a debate derived from a dissonant perception by society about the actual significance of the COVID-19 pandemic. The Brazilian population has divided into two contrasting philosophical approaches: the universalism—understanding life as an asset of infinite value and, therefore, more important than the country’s economic preservation—and the utilitarianism—where the focus is on the mitigation of the COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 31 publications
0
26
0
2
Order By: Relevance
“…This paper described some personality traits that fit the universalist profile, and others the utilitarian postulated by (Joia and Michelotto, 2020). In this way it can help to understand the macro category of Brazilian social reality nowadays and the way the brazilian Society are facing the Covid pandemic.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This paper described some personality traits that fit the universalist profile, and others the utilitarian postulated by (Joia and Michelotto, 2020). In this way it can help to understand the macro category of Brazilian social reality nowadays and the way the brazilian Society are facing the Covid pandemic.…”
Section: Discussionmentioning
confidence: 93%
“…We observed in our data an increase in psychological distress for this group (people who engaged in social isolation to comply with governmental recommendations). This can be partially explained by a phenomenon that, in the macrocontext, (Joia and Michelotto, 2020), explained as universalism x utilitarianism. The authors pointed out that the pandemic made explicit that the Brazilian population is divided into two contrasting philosophical approaches: the universalism-understanding life as an asset of infinite value and, therefore, more important than the country's economic preservation-and the utilitarianism-where the focus is on the mitigation of the Covid 19 pandemic-enabled economic crisis.…”
Section: Discussionmentioning
confidence: 99%
“…15 In the same direction, a qualitative research reported that, for Brazilians, aspects related to health and preservation of life occupy a prominent place in symbolic constructions about the pandemic. 16 A study conducted in July 2020 identified that 53% of respondents had high levels of fear of COVID-19, with higher scores among young adults, especially among those who cohabited with people belonging to risk groups for worsening the disease. 17 This may be related, according to the authors, to the fact that the pandemic may have led young people to reflect on their own mortality and that of their families.…”
Section: Discussionmentioning
confidence: 99%
“…These seven hypotheses have concrete repercussions on educational actors (teachers and students alike); consequently, they were addressed in such a way that educational and learning competencies could be promoted while the education system could be enabled towards sustainable development. Having noticed that people responded in specific ways to the SARS-Cov-2 pandemic [1,2], we investigate how students and educators reacted to the reality of online teaching implemented in response to the SARS-Cov-2 pandemic, but we did so from the perspective of the students (the questionnaire focuses on student perceptions).…”
Section: Introductionmentioning
confidence: 99%
“…Since this article is an attempt to investigate the challenges and opportunities that traditional, onsite, and face-to-face institutions face in commuting to online education, the set of research questions that lay at the foundation of this research is listed below: (1) What level of fatigue did education professionals experience following the enforcement of online activities? (2) Is the lack of human interaction (poor internet connection/the lack of electronic devices/the lack of digital proficiency/the lack of conditions of participation in class time) a key aspect of professional dissatisfaction? (3) Are professional duties sufficiently clear for educational practitioners to perform adequately?…”
Section: Introductionmentioning
confidence: 99%